2022
DOI: 10.1002/admi.202201597
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Lignin Sulfonation for Highly Conductive Wood/Polypyrrole Porous Composites

Abstract: features low-cost, low-toxicity, and pseudocapacitive behavior, and can be produced by aqueous synthetic chemical routes. [2] The conductivity of PPy is derived from the conjugated double bonds in its backbone and can reach up to 100 S cm −1 after oxidation. [3] PPy has already been used in conjunction with wood or wood-derived materials for the production of green electronics and electrochemical devices. [4] Through the bottom-up approach, pyrrole has been polymerized on cellulosic materials such as nanocellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…We summarized various cellulose-based conductive platforms as reported in the literature in Table . The obtained electrical conductivity of the vacuum-filtered membrane of 12PPy@LCNF is higher than what was reported for composites of nanocellose/PPy or nanocellulose/reduced graphene oxide (rGO). , In some studies, the monolith fabrication was carried out through in situ polymerization of pyrrole within the paper substrate or wood tissue, which restricted the processability. ,, In this perspective, the facileness to process PPy@LCNFs as various solid forms is advantageous in adapting versatile scenarios in building bioelectronic interfaces and devices. It is worth noting that the protonation level of PPy strongly depends on the experimental conditions of its preparation.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…We summarized various cellulose-based conductive platforms as reported in the literature in Table . The obtained electrical conductivity of the vacuum-filtered membrane of 12PPy@LCNF is higher than what was reported for composites of nanocellose/PPy or nanocellulose/reduced graphene oxide (rGO). , In some studies, the monolith fabrication was carried out through in situ polymerization of pyrrole within the paper substrate or wood tissue, which restricted the processability. ,, In this perspective, the facileness to process PPy@LCNFs as various solid forms is advantageous in adapting versatile scenarios in building bioelectronic interfaces and devices. It is worth noting that the protonation level of PPy strongly depends on the experimental conditions of its preparation.…”
Section: Resultsmentioning
confidence: 94%
“…This redox couple potentially permits electronic interactions between lignin and the electrochemically active material, thus enabling reversible charge-transfer in an integrated system. Several reports have also confirmed that lignin effectively enhances the capacitance of pseudocapacitive polymers, including PPy. As another thread, the complexation of lignin with Fe­(III) ions is well-documented and has been integrated in the design strategy for processing lignin-containing or lignin-derived functional materials. Inspired by the use of azo-dye to form a complex with Fe­(III) ion as a soft template to guide the synthesis of 1D pristine PPy, we came up with the approach to use LCNF as the PPy morphology modulating hard template that we described here (Scheme ). As lignin is preserved on the fibril surface, we hypothesize that it acts as immobilization domains for Fe­(III) ions and consequently confines the polymerization of pyrrole by providing nucleation sites on the fibril surface, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The sulfonated pine wood veneers were prepared according to the protocol reported previously . In brief, 2.5 g of pine veneers was wetted in deionized water and subsequently sealed in an acid digestion vessel (45 mL, Parr Instruments) containing 40 mL of a 0.7 M Na 2 SO 3 solution at pH 7 (adjusted with H 2 SO 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work, we have developed a facile in situ lignin sulfonation process under subcritical conditions for the fabrication of conductive wood composites with polymers such as poly­(3,4-ethylenedioxythiophene) (PEDOT):poly­(styrene sulfonate) (PSS) and polypyrrole. , In this work, transparent thin wood films were prepared from sulfonated pine veneers by densification using hot pressing. The preserved lignin and lignosulfonates in wood structure were exploited as a natural binder and UV-blocking material.…”
Section: Introductionmentioning
confidence: 99%
“…The former is pseudocapacitive active materials such as manganese dioxide, cobalt hydroxide, polypyrrole were added to wood-derived carbon materials to increase their capacitance [22][23][24]. The latter is to enrich the electrode materials of double-layer capacitor, such as heteroatom doping, adjusting the surface shape and etching of carbon materials [25][26][27][28][29][30][31]. Many researchers have explored this method, such as B, O and N co-doped biomass derived graded porous carbon (382.5 F g -1 at 1 A g -l ) [60], the preparation of the B doped wood derived porous carbon (285.6 F g -1 at 1 A g -1 ) [49], and N doped biomass carbon (261 F g -1 at 0.5A g -1 ) [35] exhibited no special morphological characteristics, leading to a relatively low speci c surface area and thus a low contribution rate of the pseudocapacitance [32][33][34].…”
Section: Introductionmentioning
confidence: 99%